Influence of dietary Cinnamon Oil Supplementation on Performance and Carcass Characteristics in Broilers - Ciftci, M.; Dalkilic, B.; Cerci, I. H.; Guler, T.; Ertas, O. N.; Arslan, O. (Garuda Scientific Publications, 2009)
To study the effects of dietary antibiotic (avilamycin) and cinnamon oil supplementation on broilers performance, 240 5-day-old commercial broiler chicks (Ross-308) were divided into 4 equal groups and randomly assigned to four treatment diets with four replicates. Experimental groups were; corn-soybean meal basal diet (Control), basal diet supplemented with 10 mg/kg Avilamycin (Antibiotic), 500 or 1000 ppm of cinnamon oil (C500, C1000). Birds receiving the diet containing 500 ppm cinnamon oil showed the highest average daily gain with best feed conversion efficiency. In conclusion, cinnamon oil, at a dose of 500 ppm, could be used as an alternative to antibiotic for growth promotion in broiler diets.
Keywords: Broiler; cinnamon oil; antibiotic; performance; carcass weights; carcass characteristics